Knowledge, Attitudes, and Practice Toward Prevention of COVID-19 Among Jimma Town Residents: A Community-Based Cross-Sectional Study - Bukata, Iyasu Tadesse; Dadi, Lelisa Sena; Ayana, Andualem Mossie; Mengistu, Demelash; Yewal, Delnesa; Gizaw, Tariku Sime; Woldesenbet, Yohannes Markos (Frontiers in Public Health, 2022)
Background: COVID-19 was first reported by the World Health Organization on the 31st December 2019 and later on it was declared as a global pandemic on 12th March 2020. Till now, it is a great challenge to the world and Ethiopia. To attain effective prevention and control of COVID-19pandemic, improving the knowledge, attitude, and practices of the community is necessary. Objective: To assess, knowledge, attitudes and practice, and associated factors of COVID-19 among Jimma Town residents. Methods: A community-based cross-sectional study was done among 1500 Jimma town residents from May through June /2020. Adults aged ≥18 years were included in the study. Data were collected using a structured questionnaire adapted from different literature. A face-to-face interview was implemented to collect data. Analysis was done by using SPSS version 22. A p-value of < 0.05 was used to declare statistical significance. Result: A total of 1500 participants were enrolled in the study. The majority of the respondents were female (59.3%). About 841(56.1%) of the participants had knowledge about COVID-19. Educational status, household wealth index, and employment showed association with knowledge of COVID-19. Government-owned television (37.3%) was the primary source of information about COVID-19 in |Jimma population. Only 46.6% of respondents had good attitudes towards the COVID-19 pandemic and about 638 (42.5%) of the study participants had good practice towards COVID-19. The mean practice score was 1.98 (± 0.319). Study participants who were residing at the skirt of the town were 0.37 less likely to have good practice regarding COVID-19 prevention measures than those around the center of the Town. Whereas, households with a family size of 4 to 5 individuals were 1.4 times more likely to have good practice against COVID-19 compared to households with less than or equal 3 individuals (AOR: 1.41; CI: 1.05, 1.91). Conclusion: Jimma town community has low knowledge, attitude, and practice regarding COVID-19. Knowledge, attitude, and practice scores regarding COVID-19 are significantly related to educational status, being self-employed, occupation, marital status, residence, family size, and household relative wealth index. Preventive health advisories to upraise knowledge, attitude, and practice are crucial to prevent and control COVID-19.